Studi Parametrik Rancangan Modul Penyerap Impak Mekanisme Deformasi Plastis Tipe Axial Crushing - Idznur Rizky Muhammad; Musthafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Transportation system is an important fulfillment to simplify life in this modern era. The rising crowds in traffic is parallel with the rising of accidents. This make safety is a mandatory to noticed and a primary research on vehicles. A model of a safety system is the application of crashworthiness technology. Crashworthiness is the ability of a structure to protect cargo or passenger when a collision or impact loads take place. An application design of crashworthiness on vehicles is the Impact Absorption Module. This module is responsible for the energy absorption when a collision happen on vehicles. The module designed in this research is an axial crushing design. The research is done by using finite element method simulation. Comparison of material test in this research show that the best material for impact energy absorption is Aluminium A6063 T6. Results also show the optimum design parameter on cross-section variations is the circular cross-sectioned. The parametric study shows the optimum design parameter is on D/t 20 and L/D 3.27 ratio. This design parameter is taken based on the CFE percentage that effected by the MCF and PCF impact absorption module of 76.176%.Keyword : Crashworthiness, Impact Absorption Module, Axial Crushing, Finite Element Simulation